Nahdlatul Ulama's Identity Between Social and Political Organizations - Sabarudin, Didin (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
Although Nahdlatul Ulama has positioned itself to return to khittoh, the establishment of the Partai Kebangkitan Bangsa (PKB) in 1998 shows the political identity of this organization. In turn, the Kyai became central figures in playing the social and political role of Nahdlatul Ulama. This article focuses on examining the identity relationship of the Kyai Nahdlatul Ulama in the social and political space in Indonesia. This article uses a qualitative method characterized by naturalistic descriptiveness. This article uses a critical paradigm to capture and analyze special relationships in the dynamics of identity construction of NU and PKB. The results of the study show that the factors of nomos, doxa, habitus, conjuncture, actors, capital, and dimensions in Bourdieu's social concept are correlated with kyai and ulama as the dominant factors that color and influence the journey of the two organizations. The optimization of the social capital of NU and PKB is the mainstream of political forces facing the executive and legislative elections. Charismatic leadership and the similarity of mabda' siyasi are two important factors that determine the direction, steps, and orientation of the two organizations to be inclusive or exclusive.